Pengaruh Hujan Terhadap Dosis Terbaik Koagulan PAC Untuk Menyisihkan Kekeruhan Air Baku di Pekanbaru - Fitria, Dewi; Putri, Anggi Safriyana; Asmura, Jecky (Al-Ard: Jurnal Teknik Lingkungan, 2026)
The Siak River is a source of raw water for drinking water in Riau. The water quality of the Siak River is influenced by the season. In the rainy season, turbidity usually increases so that it can affect the drinking water treatment process at the Drinking Water Treatment Plant (IPAM). The main treatment process at IPAM to reduce turbidity that is widely used is coagulation and flocculation. The level of water turbidity will affect the coagulant dose in the coagulation flocculation process. This study aims to determine the effect of rainfall on the dose and efficiency of PAC (Poly Aluminum Chloride) coagulant in the coagulation flocculation process, in addition to providing recommendations for a comparison of PAC coagulant doses before and after rain to IPAMs that take the Siak River as a source of raw water. River water samples were taken for a week in a row before and after rain. The method used to determine the best dose in this study was the trial and error method with a fast stirring speed of 120 rpm for 1 minute and a slow stirring speed of 40 rpm for 20 minutes and sedimentation for 15 minutes with water pH conditioning of 7. The results showed that the increase in river water turbidity after rain caused the need for PAC doses to increase. Before the rain, the turbidity of the Siak River water was 36.29 - 63.4 NTU and a dose of 50 mg/L was obtained as the best dose to reduce turbidity with an efficiency of 99.17%. While after the rain, the turbidity of the river water reached 129.8 - 165.7 NTU. The best dose obtained was 60 mg/L with a turbidity removal efficiency of 99.38%.